Ubiquitous and personalised contextual biomonitoring. (10th March 2009) - Andrei Dragoi, O.; Kara, Nadjia
Biomonitoring services can reduce healthcare costs and improve the quality of life by keeping a person longer in the community. This paper describes the challenges in building a remote biomonitoring system that is aware of both the environmental and the biomedical context of the subscriber. Starting from requirements identified in typical biomonitoring scenarios, a biomonitoring architecture was devised. This was refined and validated through a prototype that combines context-adaptation and awareness with the ubiquity of 3G network-coverage to allow more personalised monitoring and to better streamline information between the various healthcare players. One of the prototype goals was easy customisation and extensibility with additional inference rules, actions, and context information types and sources.